Pengembangan Kompetensi Melalui Pendidikan Lanjutan Pegawai Negeri Sipil Pada Sekretariat Daerah Provinsi Sulawesi Barat - Hernawati; Muh. Syarif Ahmad; Wahyu Nurdiansyah N (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2025)
Human resources in the organisation are an important factor as the main driver in achieving organisational goals, the existence of employees who have good competence will contribute to the completion of the tasks and responsibilities assigned to each employee, but in reality not all organisations have employees with the competencies needed by the organisation, so strategic steps are needed in creating a work atmosphere that supports the achievement of organizational goals through increasing employee competence. Based on this problem, this study aims to determine competency development through further education of Civil Servants at the Regional Secretariat of West Sulawesi Province. This research uses a qualitative method with a descriptive approach to provide a real, logical, factual and accurate description of the data that occurs in the field through data collection techniques (document review, observation and interviews). The data obtained was analysed based on competency development through further education at the Regional Secretariat of West Sulawesi Province. The results of this study indicate that employees of the Regional Secretariat of West Sulawesi Province who realise the importance of self-development tend to be more committed to pursuing further education, employees value education as an investment in future career development. Continuing education is a selling point and added value to be more confident.